CEA but not CA19-9 is an independent prognostic factor in patients undergoing resection of cholangiocarcinoma. Issue 1 (December 2017) - Loosen, Sven; Roderburg, Christoph; Kauertz, Katja; Koch, Alexander; Vucur, Mihael; Schneider, Anne; Binnebösel, Marcel; Ulmer, Tom; Lurje, Georg; Schoening, Wenzel; Tacke, Frank; Trautwein, Christian; et al.
Abstract Cholangiocarcinoma (CCA) represents a rare form of primary liver cancer with increasing incidence but dismal prognosis. Surgical treatment has remained the only potentially curative treatment option, but it remains unclear which patients benefit most from liver surgery, highlighting the need for new preoperative stratification strategies. In clinical routine, CA19-9 represents the most widely used tumor marker in CCA patients. However, data on the prognostic value of CA19-9 in CCA patients are limited and often inconclusive, mostly due to small cohort sizes. Here, we investigated the prognostic value of CA19-9 in comparison with other standard laboratory markers in a large cohort of CCA patients that underwent tumor resection. Of note, while CA19-9 and CEA were able to discriminate between CCA and healthy controls, CEA showed a higher accuracy for the differentiation between CCA and patients with primary sclerosing cholangitis (PSC) compared to CA19-9. Furthermore, patients with elevated levels of C-reactive protein (CRP), CA19-9 or CEA showed a significantly impaired survival in Kaplan-Meier curve analysis, but surprisingly, only CEA but not CA19-9 represented an independent predictor of survival in multivariate Cox-regression analysis. Our data suggest that CEA might help to identify CCA patients with an unfavourable prognosis after tumor resection.